INOS Activity Modulates Inflammation, Angiogenesis, and Tissue Fibrosis in Polyether-Polyurethane Synthetic Implants. (27th May 2015) - Cassini-Vieira, Puebla; Araújo, Fernanda Assis; da Costa Dias, Filipi Leles; Russo, Remo Castro; Andrade, Silvia Passos; Teixeira, Mauro Martins; Barcelos, Luciola Silva
Abstract : There is considerable interest in implantation techniques and scaffolds for tissue engineering and, for safety and biocompatibility reasons, inflammation, angiogenesis, and fibrosis need to be determined. The contribution of inducible nitric oxide synthase (iNOS) in the regulation of the foreign body reaction induced by subcutaneous implantation of a synthetic matrix was never investigated. Here, we examined the role of iNOS in angiogenesis, inflammation, and collagen deposition induced by polyether-polyurethane synthetic implants, using mice with targeted disruption of the iNOS gene (iNOS −/− ) and wild-type (WT) mice. The hemoglobin content and number of vessels were decreased in the implants of iNOS −/− mice compared to WT mice 14 days after implantation. VEGF levels were also reduced in the implants of iNOS −/− mice. In contrast, the iNOS −/− implants exhibited an increased neutrophil and macrophage infiltration. However, no alterations were observed in levels of CXCL1 and CCL2, chemokines related to neutrophil and macrophage migration, respectively. Furthermore, the implants of iNOS −/− mice showed boosted collagen deposition. These data suggest that iNOS activity controls inflammation, angiogenesis, and fibrogenesis in polyether-polyurethane synthetic implants and that lack of iNOS expression increases foreign body reaction to implants in mice.